Analysis of Ex Disposal Area Land Use for Fisheries Activity (Ponds) in Segara Anakan regency Based on Geography Information System - Ain, Churun (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2011)
Dredging  Segara  Anakan  lagoon  that  have  been  implemented  in  1997  -     2005,  has  given  rise  to  the consequences of new land from the dredging is often referred as Ex-Disposal Area. Along with the increasing socio-economic problems, this land is considered as a strategic area for use as aquaculture lands. Milk Fish (Chanos chanos) and Crab (Scylla sp) are comodity targets,that wants develop as silvofisheries program. This study aimed to determine the location and potential areas as aquaculture lands based on a suitability analysis.  The research method was descriptive case study, in which a purposive sampling technique was applied to collect the samples,  including 2 sampling periods (rainy and dry season). The location in this research was Ex Disposal Area (EDA), consist of Klaces, Panikel  and  Ujunggagak  district. Research  variabel  were  soil  quality,  water quality  and  EDA’s  environment parameters. Spatial analysis data used GIS, that was proccessed by ER Mapper 7.0 and ArcGIS 9.3 software. The concept of suitability level by scoring method combining values and weight matrix. Result of research yielded that potential land for fisheries activity (brakish water ponds)  were : moderately suitable class (S2) that was 5.309,05 m2, at  Panikel and  Ujunggagak districs; marginally suitable class (S3) is 77.325.77 m2, not suitable for present time class (N1) that was 1.365.955,67 m2, and permanently unsuitable class (N2) is 7.583.809,51 m2. Coverage area of class S3,N1 and N2 included Panikel, Klaces and Ujunggagak. Keywords : Land Use, Ex Disposal Area (EDA), Ponds, Geography Information System (GIS)